Generic structure and appraisal use in English article reviews written by Indonesian EFL doctoral students - Fitriati, Sri Wuli; Ghasani, Betari Irma (Universitas Islam Sultan Agung, 2024)
A journal article review is an academic writing that summarizes and assesses others’ research-based articles. For doctoral students, reviewing a journal article is usually to train them for building their argument and broadening their knowledge of an issue. The purpose of this study is to investigate the quality of article reviews written in English by one class consisting of twelve Indonesian EFL doctoral students in their first semester at a university in Semarang, Indonesia. Twelve reviews written by the students were collected. The evaluation of their writings is based on Systemic Functional Grammar, particularly the interpersonal metafunction analysis, that is, the analysis of generic structure and appraisal. Therefore, this study employs textual analyses. The analysis of generic structure refers to the template from the Writing Centre of Thompson Rivers University, and the analysis of appraisal follows Martin and White’s appraisal system (2005). The discussion of this article explains the generic structure and lexico-grammatical realizations of evaluative stances used by the students. The findings indicate that not all doctoral students can organize their review following the generic structure and optimize the use of appraisal items. This exploratory investigation provides some pedagogical implications for the teaching of academic writings in EFL contexts.